New perspectives in glioblastoma antiangiogenic therapy - Popescu, Alisa Madalina; Purcaru, Stefana Oana; Alexandru, Oana; Dricu, Anica (Contemporary Oncology/Współczesna Onkologia, 2016)
Glioblastoma (GB) is highly vascularised tumour, known to exhibit enhanced infiltrative potential. One of the characteristics of glioblastoma is microvascular proliferation surrounding necrotic areas, as a response to a hypoxic environment, which in turn increases the expression of angiogenic factors and their signalling pathways (RAS/RAF/ERK/MAPK pathway, PI3K/Akt signalling pathway and WTN signalling cascade). Currently, a small number of anti-angiogenic drugs, extending glioblastoma patients survival, are available for clinical use. Most medications are ineffective in clinical therapy of glioblastoma due to acquired malignant cells or intrinsic resistance, angiogenic receptors cross-activation and redundant intracellular signalling, or the inability of the drug to cross the blood-brain barrier and to reach its target in vivo . Researchers have also observed that GB tumours are different in many aspects, even when they derive from the same tissue, which is the reason for personalised therapy. An understanding of the molecular mechanisms regulating glioblastoma angiogenesis and invasion may be important in the future development of curative therapeutic approaches for the treatment of this devastating disease.